Retirement, intergenerational time transfers and fertility - Peter Eibich; Thomas Siedler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Retirement increases the amount of leisure time. Retired parents might choose to invest some of their time into their adult children, e.g. by providing childcare. Such intergenerational time transfers can have important implications for retirement and family policies. This paper estimates the effects of parental retirement on their adult children's fertility and labor supply. We use a representative household panel dataset from Germany to link observations on parents and adult children, and we exploit eligibility ages for early retirement using a regression discontinuity design for identification. The results show that early parental retirement induces a significant and considerable increase in (adult) children's fertility. It also decreases labor supply of daughters. The analysis of time use data shows that retired parents provide childcare and assist their children with domestic duties. The findings suggest that early retirement policies can have important spillover effects on younger generations.
Keywords: J13; J22; J26; 330